Creación y aplicación de un modelo de evaluación de la calidad del servicio orientado a 5 instituciones privadas según correspondan a la actividad económica "Recreación y Entretenimiento" en la ciudad de Guayaquil. - Mendoza Constante, Leslye Yael (2014)
The objective of this project is to create and implement a model to evaluate service quality in private institutions by economic activity, recreation and entertainment in the city of Guayaquil. A questionnaire was made with 119 questions that form a cross matrix by 17x7, the following model is from Baldrigde - Malcolm, that promotes the best quality management practical’s and the Servqual model, it is helpful to measure, evaluate and manage quality analysis services, conducting 400 interviews in five private institutions randomly. Time survey takes about 20 minutes, as is the way to evaluate quantitatively with an equivalent of 1 to 10, where 10 is the highest score and 1 being the lowest. The surveys were entered into SPSS program, where all questions were summed and the rating of customers was obtained, the results were put in the evaluations of the service quality obtained from the VCS (Value of the quality of service), getting as a result the lowest score of 7.69 and the highest score of 8.42. There by it is proven that these institutions can improve the quality of service to provide better customer service and so to satisfy the customer’s expectations have when getting the service.